Poziomy funkcjonowania dychotomii w filmie Wygnanie Andrieja Zwiagincewa - Przybysz, Anna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The aim of this article is to show how the levels of dichotomy function in the artistic world of The Banishment, directed by Andrei Zvyagintsev. We try to put emphasis on the Zvyagintsev’s artistic method, to show that said idea works on several levels. We are convinced that the idea of duality is present in The Banishment as externally (for example motif of split in the family) as well as internally (the category of the doppelgänger).